Microbial components and metamorphic grade of Miaolingian (Cambrian) black shales from the Burin Peninsula, Newfoundland, Canada - Martínez-Benítez, Blanca; Mills, Andrea J.; Álvaro, J. Javier (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2025)
The analysis of microbial and palynological remains in Cambrian shales is useful for biostratigraphic and palaeoecological purposes but, in outcrops affected by contact metamorphism, also for discriminating burial and metamorphic temperatures. The microbial composition of the Miaolingian black shales from the Pleasant View Formation (Inlet Group) in the Burin Peninsula consists of monospecific cyanobacterial associations of Bavlinella faveolata, a cosmopolitan taxon that characterized eutrophication episodes in Neoproterozoic to Miaolingian times. The specimens show varying degrees of degradation under thin-section (2D) and Field Emission Gun Scanning Electron Microscopy (FEGSEM, 3D). Raman Spectra of Carbonaceous Materials (RSCM) thermometry applied to both the acritarchs and meshworks of amorphous organic matter has reported average metamorphic temperatures of 300 to 343 ºC, whereas the standardized Crystallinity Index Standard value of 0.35 suggests temperatures slightly below the anchizone-epizone boundary, established at 300 ºC. The most likely fit for the peak metamorphic contact temperature recorded in Miaolingian black-shale samples, collected close to the Upper Devonian St. Lawrence granitic intrusions, is within the 300-350 ºC interval.